Diagnostic studies on juvenile, rapidly progressive and adult periodontitis before and after periodontal therapy (II) - (:unkn) unknown (My University, 1992)
The use of antibody levels may identify subjects developing destructive periodontitis or provide markers of disease type. Clinical parameters can be used to group cases but they are incapable of detecting differences in host-susceptibility and host immune response. The validity of radial immunodiffusion (RID) as a laboratory screening method in diagnosis based on antibody quantitation has been evaluated in 36 patients before and after periodontal therapy. It was concluded that the serum IgA, IgG, IgM and parotid IgA concentration profiles, measured with RID have little value in determining the subgroups of early onset periodontitis patients but they can be used to differentiate these groups from slowly progressing adult periodontitis patients.
Keywords: Adult; Female; Humans; Middle Aged; Adolescent; Male; Saliva; Analysis of Variance; Immunoglobulin A; Immunoglobulin G; Periodontitis; Aggressive Periodontitis; Immunoglobulin M; Immunoglobulin A, Secretory